Use of ultraviolet light in graduate medical education to assess confidence among residents and fellows in handwashing instruction. Issue 1 (20th April 2022) - Aouthmany, Shaza; Mehalik, Haley; Bailey, Morgan; Pei, Mitchell; Syed, Sameer; Brickman, Kristopher; Morrison, Kayla; Khuder, Sadik
Abstract: Background: Coronavirus disease 2019 (COVID-19) has made it imperative to focus on strategies to improve hand hygiene to minimize threats of viral transmission in hospitals. Objective: We investigated the potential of using ultraviolet (UV) light as a visual tool in hand-hygiene education to bring awareness of individual handwashing effectiveness to healthcare workers. Methods: In 2020, 117 individuals participated in the simulation and completed surveys on proper handwashing technique. Of these, 114 were first-year residents and fellows. Surveys of confidence in hand hygiene were obtained before and after formal hand-hygiene education utilizing UV light with Glo Germ lotion. The UV light and Glo Germ lotion were used to identify deficiencies in individual handwashing technique. Results: With a total response rate of 97.4%, first-year residents and fellows demonstrated a significant decrease in handwashing confidence in pre- and posteducation surveys. Study participants who had had formal hand-hygiene training in the previous 3 years also indicated confidence in hand hygiene similar to those who had not had previous hand-hygiene training. Conclusions: Overall, resident interns and fellows may have falsely elevated their hand-hygiene confidence levels. However, conclusions regarding the confidence of residents and fellows individually could not be made due to sample size. Many healthcare personnel practice improper handwashing techniques, which may be improved with education and training that includes UV light.